Analisis Kemampuan Pemahaman Pembelajaran Ilmu Pengetahuan Alam Bagi Siswa Kelas IV Sekolah Dasar - Erika Agustina; M. Ferdiyansyah; Sylvia Lara Syaflin (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This study aims to determine the students' understanding ability in learning science about style material in fourth-grade students. The method in this research is descriptive qualitative. The data in this study is qualitative. Data collection techniques used in this study were interviews and documentation. Data analysis techniques in this study used data reduction, data display, and conclusion drawing/verification. The results of this study illustrate that the ability to understand science learning style material at SD Negeri 156 Palembang can be said to be high because students can understand the indicators contained in the questions, students can understand style material if practiced or applied, and the teacher provides learning videos so that students understand style material.